Metodologi Pengajaran PAI dengan Metode Pembelajaran Quantum Teaching di Madrasah Tsanawiyah Negeri 3 Batang Hari - Asmadi, Asmadi; Masobirin, Masobirin; Asshidqi, Hasbi; Amanda, Sherly; Maila, Yunis (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study aims to explore the application, challenges, and effectiveness of the quantum teaching-learning method in enhancing student engagement and learning outcomes. Utilizing qualitative research methods, the study focuses on educators as key informants to provide comprehensive insights into the practical implementation of this method. Data collection was conducted through interviews, observations, and document analysis to understand the integration of quantum teaching with various types of learning media. The findings reveal that the quantum teaching-learning method significantly improves the learning experience by combining engaging strategies with multimedia tools, fostering an interactive and student-centered learning environment. Moreover, the study identifies key challenges such as the need for teacher training and adaptability in applying this method across different educational contexts. Strategies for overcoming these challenges include continuous professional development for educators and the provision of resources to facilitate multimedia integration. The study concludes that quantum teaching-learning enhances both student motivation and learning outcomes, making it an effective pedagogical approach for modern classrooms.